Assesment of therapeuthic treatment efficiency in “Chatka” Theraphy Centre in Nowy Targ - Walaszek, Robert; Handzel, Joanna (Polish Journal of Public Health, 2010)
Introduction. Disability is a major problem of our times because of its sheer proportions. Aim. The purpose of the studies was to measure the impact of therapy on the basic daily living activities of a subject group at a therapy centre called Środowiskowy Dom Samopomocy “Chatka” (district self-help centre) in Nowy Targ, Poland. Material and method. The subjects were, in total, ten women and ten men aged 23 to forty, the majority of whom showed a moderate level of disability. The studies were conducted twice. The first study took place in October 2005, and the second one in October 2008. The Barthel Index was used for the assessment. Results and conclusions. A three-year stay at the therapy centre made a statistically significant difference to the female subjects in terms of their own personal hygiene, toilet use, their ability to climb and walk down the stairs, of dressing and undressing, as well as meal preparation. The male subjects, equally, showed statistically important changes to their personal hygiene, washing and bathing as well as dressing and undressing.